An auction mechanism for the last-mile deliveries via urban consolidation centre - Handoko, Stephanus Daniel (Institutional Knowledge at Singapore Management University, 2014)
A number of cities around the world have adopted urban consolidation centres (UCCs) to address some challenges of their last-mile deliveries. At the UCC, goods are consolidated based on their destinations prior to their deliveries into the city centre. In many examples, the UCC owns a fleet of eco-friendly vehicles to carry out the deliveries. A carrier/shipper who buys the UCC's service hence no longer needs to enter the city centre where there might be time-window and vehicle-type restrictions. As a result, it becomes possible to retain the use of large trucks for the economies of scale outside the city centre. Furthermore, time which would otherwise be spent in the city centre can then be used to deliver more orders. With possibly tighter regulation and thinning profit margin in near future, requests for the use of the UCC's service shall become more and more common. In this paper, we propose a profit-maximizing auction mechanism for the use of the UCC's service. We first formulate the winner determination problem as mixed-integer program (MIP). Then, we provide a greedy approximation algorithm to solve the MIP in reasonable time. Our experiments indicate that the proposed auction along with the greedy approximation algorithm is able to maximize the UCC's profit to near optimality with reasonable computational budget.